Pengembangan E-Modul IPA Berbasis Flipbook Digital Untuk Meningkatkan Literasi Sains Siswa SMP - Humairah, Lily Putri; Wahyuni, Sri (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2024)
This research aims to describe the validity, practicality, and effectiveness of digital flipbook-based science e-modules to improve science literacy of junior high school students. This form of development research, which was conducted at SMP Negeri 7 Jember with a total of 31 students in class VIII F, employed the ADDIE paradigm (Analyze, Design, Develop, Implement, and Evaluate). Interviews, observations, questionnaires, tests, and documentation are all used as data gathering strategies. Research instruments include validation sheets, learning implementation observation sheets, pre-test and post-test inquiries, and student response questionnaire sheets. With a very valid category, the product validity values are 88%. Results for product practicality during learning are 94% in the category of being highly practical. Based on a review of the N-gain, product efficacy results fell into the high category at 0.84, and the findings of the student response questionnaire fell into the good area at 76%. The results of this research indicate that the developed digital flipbook-based Science e-module is valid, practical, effective, and appropriate for improving students' science literacy in science learning in junior high schools.